Segmentation of fresh vegetable shoppers by product and store attributes considered for fresh vegetable purchase in Klang Valley, Malaysia - Gindi, Abdullahi Auwal; Abdullah, Amin Mahir; Ismail, Mohd Mansor; Mohd Nawi, Nolila (International Organization of Scientific Research, 2015)
Understanding consumer segment is important especially in developing effective marketing strategies. Segmentation of the consumers depend on various factors including socio demographic factors of the consumers, product line to be considered, types of retail store used, attributes of the product as well as that of the store among other factors. This study examined and segmented the fresh vegetable consumers based on the product attributes and store attributes considered by the consumers in their fresh vegetable purchases. Results of the study indicate the most important fresh vegetable attributes and that of retail formats considered by the Klang valley fresh vegetable consumers when purchasing the product. Also applying statistical analysis technique to the data collected from the fresh vegetable consumers; they were segmented into three different segments each with its peculiar characteristics that differ from the other. The result suggests that for effective marketing strategies, there is need to consider the demand of each member of segments in meeting their need as well as capturing the targeted segment.